Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pelanggan Usaha Keripik Singkong Kube Serumpun - Maya Kesumawati; Viras Alti Pidola (CV. Kalimasada Group, 2025)
Product quality is the ability of a product to perform its functions including performance, features, reliability, suitability, durability, aesthetics. Price is the amount of money that consumers exchange for the benefits of owning or using products and services. Customer satisfaction is a feeling of pleasure or disappointment that arises after comparing the estimated product performance with the expected performance. The study aims to determine the quality of the product and price on customer satisfaction in buying cassava chips kube serumpun. This study uses a quantitative research method that has 2 (two) variables, namely independent and dependent. The sampling technique uses the lemeshow formula with the accidental sampling method. Based on the results of research that has been conducted by researchers that product quality has a positive effect on customer satisfaction in buying cassava chips as evidenced by the t test which can be seen from the calculated t value of 4.325> t table 1.985 and has a sig of 0.00 <0.05. the price variable does not affect the customer satisfaction variable in buying cassava chips kube serumpun. This is proven by the t-test -2.950 <1.985 and has a sig of 0.06>0.05. for the determination coefficient test (R2) explains that product quality and price have a very strong influence on customer satisfaction in buying cassava chips kube serumpun by 71.7% while the remaining 28.3% is influenced by other variables.